New insights on the role of the retina in diagnostic and therapeutic strategies in major depressive disorder. (June 2020) - Cosker, Eve; Schwan, Raymund; Angioi-Duprez, Karine; Laprévote, Vincent; Schwitzer, Thomas
Highlights: Light therapy is a relevant treatment for unipolar non-seasonal depression. Light therapy acts through intrinsically photosensitive retinal ganglion cells. Major depressive disorder impacts retinal structure and function. The retina is a useful area for investigating the pathophysiology of major depressive disorder. Retinal electrophysiological exploration may predict drug response during depression. Abstract: Major depressive disorder (MDD) affects people worldwide. MDD treatments include antidepressants, which involve a delayed onset of action, long-term treatment, side effects and, frequently, only partial efficacy. The lack of access to the living brain, and the complex and still poorly elucidated pathophysiology of MDD, hinders treatment development. There is not only a need for new treatment strategies, but also for new approaches to investigating the pathophysiology of MDD. Light therapy is a well-established treatment acting through the retina. Since the retina is part of the central nervous system, it has been suggested as a useful area for investigating mental illness. In this article, we will first set out the evidence that MDD affects the retina's structure and function. We will then review studies evaluating the efficacy of light therapy in unipolar non-seasonal MDD. Finally, we discuss the disruption of melatoninergic pathways in MDD, its assessment through the retina and the treatment of this disruption with light therapy.